Implementation of Digital Marketing to Advance Kali Etan Tourism MSMEs in Bringin Village - Kediri - Nugraha, Rahmat Firman (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim : The aim of this research is to test and analyze digital marketing for the progress of Kali Etan Pare SMEs Design/Method/Approach : The method used in this research is a qualitative approach. The qualitative method is a method used with the aim of exploring the experiences, feelings and perceptions of the sources. In this case, the researcher uses an interview technique, where the interview technique is carried out to obtain direct information about certain conditions, and obtain data that is useful for influencing certain situations or parties. Research Findings : The research results show that the implementation of digital marketing for the advancement of Kali Etan tourism SMEs in the village of Bringin - Kediri has a significant effect Research limitations : Limitations in the use of digital marketing are still inadequate and there is a lack of employment.